1994
DOI: 10.1042/bj3030591
|View full text |Cite
|
Sign up to set email alerts
|

Purification and molecular cloning of prostacyclin-stimulating factor from serum-free conditioned medium of human diploid fibroblast cells

Abstract: We attempted to identify the factor that stimulated prostacyclin (PGI2) production using conditioned medium from cultured human diploid fibroblast cells subjected to a series of purification steps using h.p.l.c. on DEAE-5PW, Heparin-5PW, Protein-Pak 300, and an insulin-like growth factor-1 ligand affinity column. The purified prostacyclin-stimulating factor (PSF) ran as a single band with a molecular mass of 31 kDa by SDS/PAGE. Analysis of the purified PSF by C4 reversed-phase h.p.l.c. showed a single sharp pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 41 publications
0
88
0
Order By: Relevance
“…Mac25/AGM is a secreted protein of ϳ30 kDa that is identical with previously reported molecules, including insulin-like growth factor binding protein related protein-1 (IGFBP-rP1) (7-9), tumorderived adhesion factor (10), which was later renamed AGM (11,12), and prostacyclin-stimulating factor (13). Mac25/AGM contains two major domains (9), which include an amino-terminal cysteine-rich domain containing the IGFBP motif that is conserved among IGFBPs and a C-terminal Ig-like domain.…”
Section: A High Endothelial Venule Secretory Protein Mac25/angiomodumentioning
confidence: 56%
See 1 more Smart Citation
“…Mac25/AGM is a secreted protein of ϳ30 kDa that is identical with previously reported molecules, including insulin-like growth factor binding protein related protein-1 (IGFBP-rP1) (7-9), tumorderived adhesion factor (10), which was later renamed AGM (11,12), and prostacyclin-stimulating factor (13). Mac25/AGM contains two major domains (9), which include an amino-terminal cysteine-rich domain containing the IGFBP motif that is conserved among IGFBPs and a C-terminal Ig-like domain.…”
Section: A High Endothelial Venule Secretory Protein Mac25/angiomodumentioning
confidence: 56%
“…Mac25/AGM contains two major domains (9), which include an amino-terminal cysteine-rich domain containing the IGFBP motif that is conserved among IGFBPs and a C-terminal Ig-like domain. Functionally, mac25/AGM has been implicated in various biological responses: it accumulates in the blood vessels of tumors (10), preferentially binds to extracellular matrix (ECM) components such as collagen type IV (10), promotes cell spreading of the human bladder carcinoma cell line ECV-304 on collagen type IV (10), and stimulates PGI 2 production, which is a potent vasodilator (13). It has been reported that mac25/AGM increases PGI 2 production in retinal endothelial cells, resulting in an increased retinal blood flow in vivo (14).…”
Section: A High Endothelial Venule Secretory Protein Mac25/angiomodumentioning
confidence: 99%
“…IGFBP7 is a related member of the IGFBP family , cloned by several groups (Murphy et al, 1993;Akaogi et al, 1994;Yamauchi et al, 1994), which, unlike the other family members (IGFBP1-6), exhibits a low affinity for IGF but a high and specific affinity for insulin (Oh et al, 1996). IGFBP7 is a cell adhesive glycoprotein of about 30 kDa (Akaogi et al, 1994), which is regulated by proteolytic cleavage into a two-chain form by a membrane-bound serine proteinase matriptase (Ahmed et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…After quantification by measurement of the absorbance at 260 nm, 20 mg of total RNA was applied to each lane and electrophoresed on 1 % agarose gel (Sigma) containing 2.2 mol/l formaldehyde (Katayama) [34]. The RNA was then transferred to a Hybond N filter (Amersham, Buckinghamshire, UK) and fixed by baking at 80°C for 2 h. PSF cDNA was obtained according to the method described previously by Yamauchi et al [27]. The filter was hybridized with a-32 P (deoxycytidine 5 ¢-[a-32 P] triphosphate; Amersham)-labelled probe (265-bp pair PvuII / SmaIdigested PSF cDNA fragment) using a multiprimer DNA-labelling system (Amersham) at 42°C for 16 h in a solution prepared with hybridization buffer tablets (Amersham) containing 50 % formamide (Katayama).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we purified and cloned a PGI 2 -stimulating factor (PSF) corresponding to PSA from the conditioned medium of cultured human fibroblasts [26,27]. PSF is a novel peptide with a molecular weight of about 31 000 daltons, which stimulates PGI 2 production by both cultured bovine and human vascular ECs [26±28].…”
mentioning
confidence: 99%